Handbook of modeling high-frequency data in finance - Viens, Frederi G., 1969-; Mariani, Maria C.; Florescu, Ionut 1973- (Hoboken, NJ : Wiley, 2012)
'This exciting volume presents cutting-edge developments in high frequency financial econometrics, spanning a diverse range of topics: stochastic modeling, statistical analysis of high-frequency data, models in econophysics, applications to the analysis of high-frequency data, systems and complex adaptive systems in finance, among a host of others. Written, in part, on the outgrowth of several recent conferences in the subject matter and in concert with over two-dozen experts in the field, the main purpose of the handbook is to mathematically illustrate the fundamental implementation of high-frequency models in the banking and financial industries, both at home and abroad, through use of real-world, time-sensitive applications. By using examples derived from consulting projects, current research and course instruction, each chapter in the book offers a systematic understanding of the recent advances in high-frequency modeling related to real-world situations. Every effort is made to present a balanced treatment between theory and practice, as well as to showcase how accuracy and efficiency in implementing various methods can be used as indispensable tools. To by-pass tedious computation, software illustrations are presented in an assortment of packages, ranging from R, C++, EXCEL-VBA, Minitab, to JMP/SAS. Shedding light on some of the most relevant open questions in the analysis of high-frequency data, this volume will be of interest to graduate students, researchers and industry professionals'--
Includes bibliographical references and index.
Keywords: Finance -- Econometric models; BUSINESS & ECONOMICS / Finance